Um sistema evolutivo de apoio a tomada de decisão: um estudo de caso em compra eletrônica. - Santos, Genildo Nascimento dos (2009)
The performance of data manipulation through a search engine in e-commerce systems using decision support systems can be considered a complex process due to lots of information and may grow exponentially, according to research performed by the user for acquisition of equipment electronics. The import information collected by the system may influence the time to answer during the course of the search engine in accordance with the user s request. This works proposes a hybrid approach using database and genetic algorithm based on abstract data types (GAADT), to reduce the data of database dimensionality and helpful in the selection of products